УМОВИ ФОРМУВАННЯ ІНФОРМАЦІЙНОЇ КУЛЬТУРИ МОЛОДІ (Педагогіка вищої та середньої школи, 2004)
The article deals with the problem of students’ information culture forming, the ways of raising a level of information culture of Ukrainian youth.